2013
DOI: 10.1097/qad.0b013e32835ac0e1
|View full text |Cite
|
Sign up to set email alerts
|

Poor HIV control in HLA-B*27 and B*57/58 noncontrollers is associated with limited number of polyfunctional Gag p24-specific CD8+ T cells

Abstract: We concluded that an adequate number of high functional quality Gag p24-specific CD8 T cells is strongly associated with a natural HIV controller status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Several studies have demonstrated strong associations between the presence of HLA-B*27 and certain alleles of the HLA-B*57/58 supertype with improved HIV clinical outcomes in different ethnic groups [ 26 ]. In addition, our previous study found a significant association between possession of HLA*B27 alleles and good HIV clinical outcome in Thai subjects, identified by low pVL and high CD4 counts [ 11 ]. In this study, however, these protective alleles were not over-represented in VC (36.84%) compared to NC (34.69%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have demonstrated strong associations between the presence of HLA-B*27 and certain alleles of the HLA-B*57/58 supertype with improved HIV clinical outcomes in different ethnic groups [ 26 ]. In addition, our previous study found a significant association between possession of HLA*B27 alleles and good HIV clinical outcome in Thai subjects, identified by low pVL and high CD4 counts [ 11 ]. In this study, however, these protective alleles were not over-represented in VC (36.84%) compared to NC (34.69%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously suggested that the quantity of polyfunctional HIV-specific CD8 + T cells may provide a better indication of the robustness of HIV immune control. We previously found that the absolute numbers of polyfunctional HIVp24-specific CD8 + T cells were significantly higher in VC than NC, whereas the percentages of polyfunctional cells were not [ 11 ]. Taking advantage of the larger sample size and CD4 count matching in this cohort, we revisited the analysis of the functional quality in terms of percentage of cells and absolute cell numbers (calculating from CBC, CD4, and CD8 counts).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations